FRI0123 Clinical Correlates, Outcomes and Predictors of Inflammatory Ocular Disease Associated with Rheumatoid Arthritis. (15th July 2016) - Caimmi, C.; Smith, W.M.; Crowson, C.S.; Matteson, E.L.; Makol, A.
Abstract : Background: Inflammatory ocular disease (IOD) has traditionally been regarded as a severe extra-articular manifestation (ExRA) of rheumatoid arthritis (RA) with high mortality. Objectives: This study aims to evaluate IOD, namely scleritis (SC), episcleritis (EP), peripheral ulcerative keratitis (PUK) and uveitis (UV), identified in a large single-institution cohort of patients with RA to determine clinical correlates, outcomes and risk factors. Methods: A retrospective review was performed to assemble a cohort of patients with IOD among patients with RA evaluated between Jan. 1, 1996-Dec. 31, 2013. All cases met the 1987 ACR criteria for RA. Cases were compared to age- and sex-matched comparators with RA without IOD to identify risk factors. Chi-square and rank sum tests were used to compare characteristics between groups. Kaplan-Meier methods were used to analyze outcomes. Results: A total of 92 patients (69% female; mean age 62 y) were identified with IOD (33 SC, 23 EP, 21 PUK, 14 UV). Median follow-up was 4.1 years (IQR 1.5–9.4 y). Patients with EP were younger than those with UV (p=0.032). More than 80% of SC, EP and PUK patients were seropositive compared to only 62% of UV (p=0.048). Severe extra-articular (ExRA) manifestations (Malmö criteria) before IOD were more common in SC and EP than in UV and PUK, but the latter had a higher prevalence of Sjögren's syndrome (20%). Only 8% of UV had rheumatoid nodules as compared to 35% and 36% of PUK and SC. PUK and SC were more symptomatic compared to EP. EP and UV were primarily treated with topical therapy while SC and PUK often required systemic glucocorticoids, cyclophosphamide, additional DMARDs or biologic therapy. Time to resolution for first episode of IOD was significantly different between various IOD (p=0.015) and in particular longer in SC than in EP (p=0.010). More than 58% of patients with PUK, SC or UV showed a vision loss of at least 2 Snellen lines, as compared to only 11% of EP (p=0.045). Ninety IOD patients were compared to 90 age, sex and disease duration matched RA subjects without IOD (median disease duration 10.2 y vs. 9.9 y, p=0.612; median follow up 5.7 y (IQR 1.9–10.2) for IOD patients and 4.4 y (IQR 2.0–9.0) for comparators). Cases had a higher prevalence of severe ExRA (18% vs 4%, p=0.004) and dry eye syndrome (42% vs 26%, p=0.024). Ten year survival was 66% for IOD vs 64% for non-IOD subjects (HR 0.84: 95% CI: 0.48–1.50, p=0.56) (figure ). No differences were found between IOD after correcting for age. The incidence of new ExRA in 5-year follow up was higher among cases (29% vs 11%, p=0.002). Conclusions: The clinical presentation and treatments differ among the different forms of IODs in RA. Severe ExRA and dry eye syndrome increase the risk for IOD. IOD further predispose patients to develop more ExRA, increasing disease burden. In contrast to older literature, survival among IOD patients is now at least as good as in those without IOD, perhaps due to modern RA treatment strategies or secular disease trends. Disclosure of Interest: None declared